2013
DOI: 10.1093/chromsci/bmt069
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification of Tobramycin and Vancomycin by UPLC-TQD and Application to Osteomyelitis Patient Samples

Abstract: Tobramycin and vancomycin are the most commonly used antibiotics for the treatment of osteomyelitis. A sensitive and rapid method was developed for the analysis of tobramycin and vancomycin in human drainage tissue fluid. The procedure involved a simple liquid-liquid extraction of tobramycin, vancomycin and atenolol (internal standard) and separation by ultra-high performance liquid chromatography on an Acquity UPLC BEH C18 column (2.1 × 100 mm, 1.7 µm) with a mobile phase consisting of 0.1% (v/v) formic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…This is the reason why the sensitivity of MS was higher than that of PAD [ 24 ]. The TQD mass spectrometry has the advantage in quantitative analysis due to its MRM mode, which can eliminate background interference [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is the reason why the sensitivity of MS was higher than that of PAD [ 24 ]. The TQD mass spectrometry has the advantage in quantitative analysis due to its MRM mode, which can eliminate background interference [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Nevertheless, our study on patient samples showed that the local VCM concentration reached a peak at the fourth day postimplantation and then decreased rapidly, indicating unsatisfactory control over the sustained release of drug. 8,9 Therefore, a new delivery system with controlled and sustained release is crucial. Nanocarriers 10,11 have attracted prominent interest in the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical methods have been developed for measuring vancomycin in liquid samples only, such as plasma/serum, urine, human drainage tissue fluid and bronchoalveolar lavage fluid, including HPLC methods [8][9][10] and LC-MS/MS methods [11][12][13][14][15]. A few methods have been reported for the determination of vancomycin in both liquid and solid samples, such as immunoassays for plasma/serum and bone [16,17], HPLC method for plasma, bone and atrial appendage tissue [18], and LC-MS/MS for serum, perivascular fat and atrial wall samples [19].…”
Section: Introductionmentioning
confidence: 99%